Webbed Type of Integrated Science Learning on the Theme of Environmental Pollution to Improve Students’ Scientific Literacy - Widharnati Widharnati; Rita Retnowati; Irvan Permana; Tamara Rončević (Universitas Pakuan, 2022)
This study aims to get information on how to integrate the science learning type of Webbed with the theme of environmental pollution to improve students’ scientific literacy. The subject of study was seventh-grade students in middle school. The research method used in this study is a quasi-experimental method with a Nonequivalent Control Group Design. The data were analyzed by calculating the normalized gain average score to determine the increase in scientific literacy. The average result of N-Gain in students' scientific literacy as a whole obtained in the experiment class is 0.66 while the control class is 0.43, both are in the medium category with a difference of 0.23. The hypothesis test result in the t-test is known as the significance level of 0.000 which means that Ho is rejected, and Ha is accepted. Based on the result of this t-test, it is known that students’ scientific literacy abilities are not the same. This means that there were differences in the increase in scientific literacy in integrated webbed versus conventional science learning types without integration. The result of the study shows that webbed-type integrated learning can improve students’ scientific literacy on aspects of content, process, and attitude.